Kaiser Community Homes - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a man and a woman standing outside a house. The writing on the curb reads: "Newhall St." A sign reads: "Kaiser Community Homes: Santa Clara - San Jose."